Construction of Meaning that Signals the Radical Ideology in Poem “Nggahi Dana” - Irwansyah Irwansyah; Arifuddin Arifuddin; Kamaludin Yusra (IJECA (International Journal of Education and Curriculum Application), 2018)
This research aimed to describe the construction of meaning that signals the radical ideology in poem “Nggahi Dana,” which is often recited in the folk games known in Dompu regency. The meaning construction was approached using hermeneutic theory of Hans-George Gadamer and other theories, namely poststructural theory and literature sociology. The research used qualitative method with analytical description character. Data were collected through field observations with recording-video technique. Data were later transcribed with bookkeeping. Data interpretation was made using literature method. Results indicate that ideology construction in the poem “Nggahi Dana” in Dompu regency relates to societal value, philosophy, norm, religious belief, sentimentality, ethical rule, knowledge or perception about world and ethos.